2008
DOI: 10.1080/19322880802231759
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Community Cohesion on Stress Symptoms Following a Terrorist Attack

Abstract: The effects of community cohesion were explored following a terrorist attack in Israel, during which an explosion on a public bus in a metropolitan city killed and wounded multiple individuals. Participants were 115 Israelis who resided in three specified perimeters around the area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…Indeed, the unfavorable implication of urban as compared with rural residency is typically attributed to the supportive nature of a close community characteristic of rural regions, as well as the sense of belonging that such communities foster (N. R. Stein et al, 2013). This is despite the fact that community cohesion has been pre-viously linked both to symptom exacerbation and symptom reduction, depending on the level of exposure and geographical proximity of the victim to the traumatic incident (Somer et al, 2008).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…Indeed, the unfavorable implication of urban as compared with rural residency is typically attributed to the supportive nature of a close community characteristic of rural regions, as well as the sense of belonging that such communities foster (N. R. Stein et al, 2013). This is despite the fact that community cohesion has been pre-viously linked both to symptom exacerbation and symptom reduction, depending on the level of exposure and geographical proximity of the victim to the traumatic incident (Somer et al, 2008).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…The results revealed that sense of community was associated with higher levels of PTSD symptoms (Table 2), a finding that was contrary to our predictions yet, in retrospect, not entirely unexpected. Occasional empirical reports (e.g., Bryant et al., 2017; Gallagher et al., 2019; Somer et al., 2008) have suggested that, at times, more extensive connections with one's community may be a liability in the context of coping with collective upheavals. In such cases, for some survivors, reactions and behaviors aimed at sharing their feelings and concerns may inadvertently exacerbate both their symptoms and others’ symptoms of distress.…”
Section: Resultsmentioning
confidence: 99%
“…We found several prior studies with findings that give some credence to this interpretation. In an investigation of the influence of community cohesion following a terrorist incident in Israel (Somer et al., 2008), sense of community cohesion was positively related to PTSD symptoms among individuals who reported low and moderate degrees of exposure to the event. However, for individuals with a high level of trauma exposure, community cohesion and distress were inversely related.…”
Section: Discussionmentioning
confidence: 99%
“…It appears the relationship between community cohesion and trauma reactions is influenced by level of exposure. High community cohesion appears to lead to more PTSD symptoms in communities with low to moderate exposure to the traumatic event, whereas high cohesion seems to mitigate PTSD in communities with high trauma exposure (Somer et al, 2008). These authors suggested high community cohesion with low to moderate exposure may precipitate a contagion-like effect in reaction to the trauma, whereas the increased support that accompanies cohesion in the high exposure group is a protective factor.…”
Section: Application Of the Bioecological Model To Three Types Of Masmentioning
confidence: 99%